DAKWAH DIALOGIS-BERKEARIFAN TERHADAP PURIFIKASI DAN SINKRETISASI TRADISI BAKAR KEMENYAN DAN BALIMAU - Fitra Yanti; Zelfeni Wimra (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2021)
This article discusses the dynamics of purification and syncretization of the tradition of burning incense and balimau in the Minangkabau community. The aim is to explain how the dialogic-wise pattern of da'wah is against local traditions or wisdom. The method used is critical discourse analysis of the dominance of purification and syncretization discourses in da'wah. The temporary conclusion is that the pattern of preaching which should be dialogic-wise is still interpreted as a stage of purification of practices that are claimed to be syncretic. The implication is that dialogic-wise preaching becomes one of the da'wah patterns that can be mainstreamed in understanding the plurality of cultures and traditions.